Participatory dynamics with prison staff: health practice to combat tuberculosis misinformation and stigmatization (Research, Society and Development, 2020)
Objective: Narrate the experience of an active methodology applied to verify and spread the knowledge about tuberculosis among prison staff of western São Paulo State. Methodology: This is an experience report on activity applied in a dynamic and playful way, where the thematic axes and questions about tuberculosis (contagion, defense, prophylaxis, symptomatology, treatment and social aspects) were drawn, initiating a collective debate. Twenty-six professionals from CIPA (Internal Commission for Accident Prevention) participated in the activity and, at the end, completed a short questionnaire to narrate their experience with the activity, about the relevance and applicability of the topic discussed. Results: The activity promoted very productive debates, demonstrating that many still had doubts about tuberculosis. Despite being satisfied with the methodology, the participants felt the lack of printed material, or the closing with a lecture. In addition, the need to involve prison units and those deprived of liberty in health practices became clear. Conclusion: It was verified that prison staff still lacks knowledge about tuberculosis and this type of activity has the potential to be a good tool for disseminating knowledge.